2017
DOI: 10.1021/acs.orglett.7b03580
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Mediated Cascade C–H/N–H Annulation of Indolocarboxamides with Arynes: Construction of Tetracyclic Indoloquinoline Alkaloids

Abstract: An efficient and environmentally benign Cu-mediated method was developed for direct cascade C-H/N-H annulation to construct polyheterocyclic indoloquinoline scaffolds. This method highlights an emerging strategy for transforming inert C-H bonds into versatile functional groups in organic synthesis and provides a new versatile approach for the efficient synthesis of indolo[3,2-c] and [2,3-c]quinoline alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 68 publications
1
31
0
1
Order By: Relevance
“… [69] Miura et al . found that removal of MQ from benzolactams 285/286 was possible in moderate yields, but only when more forcing conditions were used (BBr 3 followed by a hypervalent iodine oxidant) [73, 175, 176] . Interestingly, Daugulis et al .…”
Section: Oxidative Cleavage Of the Amide Bondmentioning
confidence: 99%
“… [69] Miura et al . found that removal of MQ from benzolactams 285/286 was possible in moderate yields, but only when more forcing conditions were used (BBr 3 followed by a hypervalent iodine oxidant) [73, 175, 176] . Interestingly, Daugulis et al .…”
Section: Oxidative Cleavage Of the Amide Bondmentioning
confidence: 99%
“…The 3d transition‐metals like copper has grave attention toward C−H/NH annulations for the synthesis of alkaloids and biologically active molecules [62] . Similarly in 2018, Zhang and his group [63] reported C−H/N−H annulations mediated by copper to construct tetracyclic indoloquinolines (tetrahydro‐β‐carbolinones, 21 ) using CsF and TBAI in the presence of molecular oxygen from indolo‐2‐carboxamides ( 19 ). The electron‐donating and withdrawing group containing indole derivatives were participated in the reaction with significant yield.…”
Section: Synthesis Of β‐Carbolinesmentioning
confidence: 99%
“…The Zhang group developed several copper-mediated syntheses of natural products and in 2018 reported a selective cascade C-H/N-H annulation strategy toward the tetracyclic core of isocryptolepine, thus providing a new formal total synthesis of the natural product. 156 The bond forming approach is mediated by a 8-aminoquinoline N,Nbidentate directing group 157 and involves a reaction with a benzyne derivative under mild conditions.…”
Section: D Syntheses From Indolesmentioning
confidence: 99%